Assisted Interpretation of Laser-Induced Fluorescence Spectra of Egg-Based Binding Media Using Total Emission Fluorescence Spectroscopy. (28th December 2006) - Nevin, Austin; Anglos, Demetrios
Abstract : Laser-induced fluorescence (LIF) spectroscopy can provide nondestructive, qualitative analysis of protein-based binding media found in artworks. Fluorescence emissions from proteins in egg yolk and egg white are due to autofluorescent aromatic amino acids as well as other native and age-related fluorophores, but the potential of fluorescence spectroscopy for the differentiation between binding media is dependent on the choice of a suitable excitation wavelength and limited by problems in interpretation. However, a better understanding of emission spectra associated with LIF can be achieved following comparisons with total emission fluorescence spectra where a series of consecutive emission spectra are recorded over a specific range. Results using nanosecond UV laser sources for LIF of egg-based binding media are presented which are rationalised following comparisons with total emission spectra. Specifically, fluorescence is assigned to tryptophan and oxidation products of amino acids; in the case of egg yolk, fatty-acid polymerisation and age-related degradation products account for the formation of fluorophores.